Analysis of reclaimed asphalt pavement with rejuvenating materials - Ng, Cui Ming; Anis, A.; Putra Jaya, Ramadhansyah; Liew, Nicole Siaw Ing (Penerbit UMP, 2023)
Reclaimed asphalt pavement (RAP) is currently commonly used in road construction. Reclaimed asphalt pavement can enhance environmental sustainability while also reducing reclaimed pavement disposal issues. In this study, waste cooking oil (WCO) was utilized as rejuvenating material. There are different samples, where Sample A is the control mixture which is virgin mixture without rejuvenator contain 0% of RAP content. Sample B is the rejuvenated RAP mixtures including 25% and 50% of RAP content combined with WCO, while sample C is the non-rejuvenated RAP mixture containing 25% and 50% of RAP content. In addition, sample D is for 100% RAP content. Therefore, to evaluate the engineering properties, different experimental test, including Marshall stability and flow, dynamic creep modulus and indirect tensile strength are applied, and the optimum percentage was determined based on the result. The findings revealed that reclaimed asphalt pavement with rejuvenating materials enhanced the performance of stability and deformation resistance. Moreover, the indirect tensile strength increases with the increase of RAP content. Based on the findings, it can conclude that 100% of reclaimed asphalt pavement showed the optimum value and significantly enhanced the performance of reclaimed asphalt pavement with rejuvenating materials by reducing pollution.